EVALUASI EFEKTIVITAS RE-DESIGN TARGET INJEKSI DAN KEDALAMAN GAS LIFT VALVE UNTUK MENINGKATKAN PRODUKSI SUMUR X DAN Y - Fatiya Aqlin Nabila; Sari, Riska Laksmita; Triono, Agus (Petro : Jurnal Ilmiah Teknik Perminyakan, 2025)
Well production rates tend to decline due to various factors, such as reservoir pressure decline, increased water cut, and fluctuations in the Gas-Oil Ratio (GOR). These conditions cause a decrease in the efficiency of artificial lift systems, particularly gas lift systems, resulting in suboptimal production performance. This study aims to evaluate and redesign the gas lift system by determining the optimal gas injection rate and Gas lift Valve (GLV) depth to enhance oil production. The methodology involves simulation using PIPESIM software, sensitivity analysis of gas injection targets and GLV depth, and manual calculations using Microsoft Excel to identify optimal operating conditions. The results of the study show that after redesign, the optimal gas injection rates are 6.25 MMscf/d for well X and 7.2 MMscf/d for well Y, with GLV depths at 3400 ft and 3990 ft, respectively. The redesign was proven to increase oil production by 281.80 stb/d (4.01%) for well X and 345.12 stb/d (12.01%) for well Y, while maintaining production performance at increasingly higher water cuts and minimizing the peak optimal value of GOR fluctuations. Thus, the gas lift system redesign is deemed effective in increasing well production and supporting long-term operational sustainability.